Prospective study on nanoparticle albumin-bound paclitaxel in advanced breast cancer: clinical results and biological observations in taxane-pretreated patients - Fabi, Alessandra (Drug Des Devel Ther, 2015)
BACKGROUND: There is a deep need to improve the care of metastatic breast cancer (MBC) patients, since even today it remains an incurable disease. Taxanes are considered the most effective cytotoxic drugs for the treatment of MBC, both in monotherapy and in combined schedules, but the need for synthetic solvents contributes to the severe toxicities and may have a negative impact on the efficacy. Nanoparticle albumin-bound paclitaxel (Nab-paclitaxel) is a colloidal suspension of paclitaxel and human serum albumin initially developed to avoid the toxicities associated with conventional taxanes. PATIENTS AND METHODS: The aim of this prospective, single-center open-label, noncomparative study was to evaluate the efficacy and safety of nab-paclitaxel in MBC patients pretreated with taxanes. The patients were treated with nab-paclitaxel as a single agent, 260 mg/m(2) on day 1 of each 3-week cycle or 125 mg/m(2) weekly. The primary endpoint was the overall response rate (ORR). Secondary objectives were duration of response, clinical benefit rate, progression-free survival (PFS), overall survival, and safety. RESULTS: A total of 42 patients (median age 48 years, median Eastern Cooperative Oncology Group performance status 0, triple-negative MBC 19%, all pretreated with a taxane-based therapy, mainly in advanced disease) were enrolled in the study. The ORR was 23.8%, including one complete response (2.4%) and nine partial responses (21.4%); the disease control rate was 50%. The median duration of response was 7.2 months. After a median follow-up of 9 months, the median PFS was 4.6 months. ORR and PFS were similar irrespective of the previous chemotherapy lines, metastatic sites, and biomolecular expression. Nab-paclitaxel was well tolerated, and the most frequent treatment-related toxicities were mild to moderate (grades 1–2). CONCLUSION: This real-life study shows that nab-paclitaxel has a significant antitumor activity and a manageable safety profile in patients pretreated with taxanes and experiencing a treatment failure after at least one line of chemotherapy.